2019
DOI: 10.1519/jsc.0000000000001881
|View full text |Cite
|
Sign up to set email alerts
|

Neuromuscular Adaptations to Short-Term High-Intensity Interval Training in Female Ice-Hockey Players

Abstract: High-intensity interval training (HIIT) related neuromuscular adaptations, changes in force production and on-ice performance were investigated in female ice-hockey players during pre-season. Fourteen Finnish championship level ice hockey players (average age 22 ± 3 years) participated in 2½-week HIIT. Both spinal (H-reflex) and supraspinal (V-wave) neuromuscular responses of the soleus muscle were recorded before and after the training period. Static jump (SJ) and countermovement jump (CMJ) heights, plantar f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 29 publications
0
38
0
Order By: Relevance
“…Shortcomings in the study of Kinnunen et al ( 2017 ) were the missing transfer of the results to increased sport specific performance (e.g., faster skating times on ice). Compared to the current study, in the study by Kinnunen et al ( 2017 ) a shorter training period (2.5 vs. 9 weeks) and shorter HIIT bouts (30 s vs. 4 min) were applied. The question remains which training period durations using different training regimes (e.g., HIIT protocols) are necessary for these improvements.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Shortcomings in the study of Kinnunen et al ( 2017 ) were the missing transfer of the results to increased sport specific performance (e.g., faster skating times on ice). Compared to the current study, in the study by Kinnunen et al ( 2017 ) a shorter training period (2.5 vs. 9 weeks) and shorter HIIT bouts (30 s vs. 4 min) were applied. The question remains which training period durations using different training regimes (e.g., HIIT protocols) are necessary for these improvements.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, close relationships between running performance from distances of 400–5,000 m with performance in the MART and short-duration sprint performance over 20–30 m were found in numerous studies (e.g., Rusko et al, 1993 ; Nummela et al, 1996 , 2006 , 2007 ; Paavolainen et al, 1999a , c ). In this context, neuromuscular adaptations using HIIT in ice hockey players, improved the general muscle activation as demonstrated in increased force and rate of force development in an isolated plantar flexion (Kinnunen et al, 2017 ). Shortcomings in the study of Kinnunen et al ( 2017 ) were the missing transfer of the results to increased sport specific performance (e.g., faster skating times on ice).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, both high effort resistance training (Nuzzo et al, 2017) and 'cardio' based high intensity interval training (Kinnunen et al, 2019) have been shown to strength likely due to neurmuscular adaptations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the explanation for poor force development seems to be a lack of strength training during BT, which is also supported by unchanged V-wave responses. V-wave measures neural drive from central sources and different forms of strength training have been shown to improve this response [1,7,32]. However, it should be mentioned that FFM was decreased in LF, which was not observed in GF.…”
Section: Discussionmentioning
confidence: 99%